The prevalence of chronic kidney disease among type 2 diabetes mellitus patients in central South Africa - William Mhundwa; Gina Joubert; Thabiso R.P. Mofokeng (South African Family Practice)
Background: Type 2 diabetes mellitus (T2DM) is a leading cause of chronic kidney disease (CKD). The prevalence of CKD among T2DM patients in Africa is 22.0%. The cut-off age for dialysing diabetic patients in the resource-limited state sector in South Africa is 50 years. Type 2 diabetes mellitus patients who develop CKD are likely to be excluded from chronic dialysis and rely on control of risk factors, including blood pressure and blood glucose levels, to prevent CKD progression. We aimed to determine the prevalence of CKD among T2DM patients attending the diabetes clinic at Pelonomi Academic Hospital, Bloemfontein.